Effect of Modified Atmosphere Packaging on the Refrigerated Storage of Mantı - Sinan Uzunlu; Işıl Var (Turkish Journal of Agriculture: Food Science and Technology)
Mantı, the traditional Turkish food, was subjected to modified atmosphere packaging (MAP) compositions of MAP 1 (80% CO2 + 20% N2), MAP 2 (40% CO2 + 60% N2), MAP 3 (60% CO2 + 40% N2) and control (packaged under atmospheric composition) to extend its refrigerated storage at 4°C. The physical, chemical and sensorial qualities of each package were assessed by analysing headspace gas composition, pH, water activity, 2-thiobarbituric acid (TBA), dry matter, lipid content and a sensory analysis of both cooked and raw mantı samples. The compositions of MAP samples (MAP 1, MAP 2 and MAP 3) resulted in the maximum storage time of 126 days versus 20 days in normal atmospheric packaging (control). In conclusion, 60% CO2 or either 80% CO2 with N2, as a make-up gas, should be implemented in the mantı process.